Development of Tools and Database for Analysis of Metal Binding Sites in Protein - Kumar Kuntal, Bhusan; Aparoy, Polamarasetty; Reddanna, Pallu (Protein and Peptide Letters, 2010)
In this study, we have developed a standalone tool called as ANAMBS (Analysis of Metal Binding Site) to derive metal neighbourhood information using PERL as the programming language. The tool accepts the structures in the pdb format. The cut off distance to define the metal binding region can be specified. The metal binding site composition, orientation of various amino acids and atoms along with the Hydropathy index within the metal binding site region can be measured. Its speed and efficiency makes it a beneficial tool for various structural biology projects, especially when the characterization of the metal binding domain is needed. Additionally, the database MEDB (Metal Environment Database) was developed which presents quantitative information on metal-binding sites in protein structures. It can be used for identification of trends or patterns in the metal-binding sites. The information obtained can be used to generate structural templates from metal binding sites of known enzymes and to develop constraints for computational modeling of metalloproteins. The tool and database are available at http://www.uohyd.ernet.in/anambs/
Keywords: metalloproteins